EFFECT OF FINANCING TO DEPOSIT RATIO AND NON-PERFORMING FINANCING OF RETURN ON ASSETS WITH A CAPITAL ADEQUACY RATIO AS VARIABLE INTERVENING IN ISLAMIC BANKING IN INDONESIA IN 2012-2019 - Lutfia Abriet Fajriati; Asmak Ab Rahman; Shinta Maharani (Niqosiya: Journal of Economics and Business Research, 2021)
Income in Islamic banks is primarily determined by how much profit or profit the bank receives. Several factors that become indicators of Islamic Bank income are financing funding and the lack of non-performing financing. The greater the financing of third-party funds, the greater the profit to be received, and the higher the NPF level, the lower the bank's profit. Banks with a large enough CAR will be able to increase bank profitability. The NPF variable harms ROA because a decrease in the NPF ratio will increase bank profits. And the CAR variable as an intervening variable also has a positive effect on ROA because an increased CAR will increase bank profitability. Whereas when the NPF decreases, the profitability of Islamic banks also decreases, while when FDR and CAR increase, ROA decreases. The formulation of the problem in this study is whether there is a partial and simultaneous influence of FDR and NPF on ROA?. Is there a partial and simultaneous influence of FDR, NPF, and CAR on ROA. This research is a quantitative study with the population of Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK). In comparison, the sample of this study was determined by purposive sampling method with criteria determined by the researcher so that 4 Islamic commercial banks were obtained from 2012 to 2019. This study used secondary data with research methods using quantitative methods with an associative approach. Data collection techniques were carried out by observation. The data analysis technique used in this research is the associative analysis technique, namely multiple linear regression testing, classical assumption test, hypothesis testing, coefficient of determination test, and path analysis. The results of this study indicate that partially the FDR variable has an insignificant negative effect on ROA, NPF has a significant negative effect on ROA. In comparison, CAR has a positive and significant effect on ROA. Simultaneously, the FDR and NPF variables have no significant effect on ROA. For the results of the path analysis, it is found that the CAR variable cannot mediate the effect of FDR and NPF on ROA.